From the shallow to the mesophotic: a characterization of Symbiodiniaceae diversity in the Red Sea NEOM region - Terraneo, Tullia I.; Ouhssain, Mustapha; Castano, Carolina Bocanegra; Aranda, Manuel; Hume, Benjamin C. C.; Marchese, Fabio; Vimercati, Silvia; Chimienti, Giovanni; Eweida, Ameer A.; Voolstra, Christian R.; Jones, Burton H.; Purkis, Sam J.; et al. (Frontiers in Marine Science, 2023)
The northern Red Sea has been coined a refuge for reef corals due to the exceptional thermal tolerance of these organisms. With ocean warming threatening coral reefs worldwide, a panoptic characterization of corals living in extreme conditions may provide insights on future responses of corals to environmental change. Among other factors, the genotype of the endosymbiotic algae in the family Symbiodiniaceae has been shown to have major implications on the distribution and resilience of their coral hosts. In this work we aim at genotyping the Symbiodiniaceae communities associated with three depth generalists and one depth specialist coral species, characterized by the ability to withstand environmental conditions apparently limiting for other corals and occurring in a unique geographical region. We sampled 50 corals from the northern Saudi Arabian Red Sea and Gulf of Aqaba covering 97 m bathymetric gradient. We used high throughput ITS2 gene sequencing and recovered different patterns of host-algal associations. The majority of the recovered algal genotypes appeared host- and environment-specific, whilst others were more widely distributed. At large, coral specimens were overwhelmingly associated with symbionts from the genus Cladocopium, and specifically with many previously underscribed genotypes. This suggests selection of specific genotypes which might confer resistance and/or resilience to their host counterparts. Interestingly, we found limited association with Durusdinium spp. and other known tolerant taxa in mesophotic corals in the northern Red Sea, but not in the Gulf of Aqaba. The broad absence of Durusdinium spp., typically ascribed to be stress tolerant, warrants further investigation into Symbiodiniaceae species that convey environmental resilience. Our data will serve as a baseline to explore the occurrence of specific symbionts which might be contributing to coral acclimation and adaptation and to assay what biodiversity might be impacted if subject to increasing stressors.